Evaluación in vitro de la actividad biocida de diferentes fungicidas sobre el crecimiento radial de Moniliophthora roreri, Moniliophthora perniciosa y Phytophthora palmivora, agentes causales de enfermedades en cacao. - Bravo Menéndez, Joel Arturo (2019)
One of the most important limitations of the cocoa crop (Theobroma cacao L) is the low productivity, whose primary cause is the attack of fungal diseases. The moniliasis whose causative agent is the fungus Moniliophthora roreri, the witch's broom caused by Moniliophthora perniciosa and the black cob caused by the pseudohongo Phytophthora palmivora. So far, there are relatively few effective fungicides against these pathogens, this study aimed to evaluate the in vitro efficiency of four chemical synthesis fungicides, fosetil aluminum, copper hydroxide, copper citrate, azoxystrobin and a tree plant extract of the tea Melaleuca alternifolia (®Timorex); all fungicides were used in individual experiments for each pathogen, in three concentrations 1000, 1500 and 2000 ppm. Using the agar plate dilution method. Copper hydroxide (®Koccide 2000) showed the greatest effect against the three pathogens showing 100% inhibition of mycelial growth in the three doses. The other products showed different behavior for each pathogen. Azoxystrobin (®Quadris) and fosetyl aluminum (®Fosetil-Al 80%) also inhibited 100% mycelial growth of P. palmivora in all three doses. In turn, copper citrate was the least efficient, allowing the mycelial growth of the three organisms even at the highest dose of 2000 ppm. The mean lethal dose (LD50) was determined for copper citrate. One aspect to be taken into account is that the sporulation of M. roreri and P. palmivora were affected by all the fungicides under study, with the exception of copper citrate whose inhibition of P. palmivora was 28.73%, 68.53% and 98.03% for the doses of 1000, 1500 and 2000 ppm respectively, the timorex allowed sporulation of M. roreri in the doses 1000 ppm (79.87%) and 1500 ppm (47.83%) of inhibition. The study allows to confirm new efficient fungicides against the three cocoa pathogens that can be incorporated into the management plans, after field efficiency tests. Keywords: Moniliophthora roreri, Moniliophthora perniciosa, Phytophthora palmivora, fungicides, LD50, pseudohongo, plant extract.